Dynamics of cytotoxic T cell subsets during immunotherapy predicts outcome in acute myeloid leukemia - Sander, Frida Ewald (Oncotarget, 2016)
Preventing relapse after chemotherapy remains a challenge in acute myeloid leukemia (AML). Eighty-four non-transplanted AML patients in first complete remission received relapse-preventive immunotherapy with histamine dihydrochloride and low-dose interleukin-2 in an international phase IV trial (ClinicalTrials.gov; NCT01347996). Blood samples were drawn during cycles of immunotherapy and analyzed for CD8(+) (cytotoxic) T cell phenotypes in blood. During the first cycle of therapy, a re-distribution of cytotoxic T cells was observed comprising a reduction of T effector memory cells and a concomitant increase of T effector cells. The dynamics of T cell subtypes during immunotherapy prognosticated relapse and survival, in particular among older patients and remained significantly predictive of clinical outcome after correction for potential confounders. Presence of CD8(+) T cells with specificity for leukemia-associated antigens identified patients with low relapse risk. Our results point to novel aspects of T cell-mediated immunosurveillance in AML and provide conceivable biomarkers in relapse-preventive immunotherapy.